Evaluation of Customer Education and Satisfaction of Prepaid Meter Usage in Nigeria Electricity Distribution Company - Kayode Alao; Kasali Jimoh; Adebayo Joseph Obadiora (Journal of Digital Learning and Education, 2022)
The study identified challenges confronts customers using pre-paid meters within Ile-Ife Metropolis, relevance of prepaid meter usage over the post-paid meter usage within Ile-Ife Metropolis and the level of customer satisfaction with respect to pre-paid meter usage. The study used descriptive research designs. The population for the study consisted 17,551. The sample for the study consisted 204 prepaid user customers selected using stratified sampling techniques. The sample was calculated using Fishers (1995) which has ideal formula for targeted population. The instrument used for the study was questionnaire namely “Customer Education and Satisfaction of Prepaid Meter Usage in Ibadan Electricity Distribution Company”. Cronbach Alpha (?) was used to test validity of the research instrument. The output gave Reliability Statistics which showed Cronbach's alpha of 0.701. Data collected were be analyzed using inferential statistics. The results showed that majority at 32.4% (66) of the sampled users of prepaid meters agreed that there has been no disconnection, and there is no need to pay a re-connection fee when using prepaid meter while 18.6% strongly disagreed with the claimed; the system is disadvantageous to the poor and showed that 5.9% (12) of the sampled customers highly dissatisfied with the respect to prepaid meter usage in Ile-Ife, 17.6 % (36) dissatisfied with the prepaid meter usage while 38.7% (79) of the customers satisfied with the usage of prepaid meter and 37.7 % (77) of the customers highly satisfied with the usage of prepaid meter in Ile-Ife. The study concluded that IBEDC should sensitizing the customers before introducing prepaid meters to them for this would enhance the level of customer satisfaction.